China's 2008 Labor Contract Law: Implementation and implications for China's workers. (February 2015) - Gallagher, Mary; Giles, John; Park, Albert; Wang, Meiyan
This article presents empirical evidence from household and firm survey data collected during 2009−2010 on the implementation of the 2008 Labor Contract Law and effects on China's workers. The Government and local labor bureaus have made substantial efforts to enforce the provisions of the new Law, which has likely contributed to reversing a trend toward increasing informalization of the urban labor market. Enforcement of the Law, however, varies substantially across cities. The article analyzes the determinants of worker satisfaction with the Law's enforcement, workers' propensity to have a labor contract, their awareness of the Law's content and their likelihood of initiating disputes, and finds that all are highly correlated with education level, especially for migrants. Although higher labor costs may have had a negative impact on manufacturing employment growth, this has not led to an overall increase in aggregate unemployment or prevented the rapid growth of real wages. Less progress has been made in increasing social insurance coverage, although signing a labor contract is more likely to be associated with participation in social insurance programs than in the past, particularly for migrant workers.